Post‐COVID‐19 Neutropenia in an Infant With Thalassemia Minor: Case Report - Yasmine Elsherif (22045415) (2025)
This case of an 11‐month‐old female who developed severe neutropenia following COVID‐19 infection underscores the need for heightened vigilance and monitoring of hematological parameters in infants post‐COVID‐19. The exact mechanism of COVID‐19‐induced neutropenia is not fully understood, but it may involve cytokine‐induced suppression of hematopoiesis and bone marrow repression due to the inflammatory response. Given the potential for serious clinical implications, including increased susceptibility to infections, it is crucial to effectively identify and manage neutropenia in this vulnerable population. Further research is necessary to elucidate the underlying mechanisms and optimize treatment strategies for COVID‐19‐related hematological complications in infants. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.9668